Measuring threshold effects in non-dynamic panels: the impact of terms of trade on FDI inflows under different regimes of institutional quality - Barone, Sergio (2019)
Fil: Barone, Sergio. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas; Argentina.